Influence of ground pumice powder on the mechanical properties and durability of self-compacting mortars - Karatas, Mehmet; Benli, Ahmet; Ergin, Abdurrahman (Elsevier Sci Ltd, 2017)
The aim of this study is to investigate the mechanical properties and durability of self-compacting mortars (SCMs) produced from ground pumice powder (GPP) as a mineral additive. In this scope, 8 series of SCMs including control mixture were prepared that consist of 5%, 10%, 15%, 20%, 25%, 30% and 35% of ground pumice powder by weight of cement. A total of 72 specimens of 40 x 40 x 160 mm were produced and cured at the age of 3, 28 and 90-day for compressive and tensile strength tests and 24 specimens of 50 mm cube specimens were prepared and cured at 28 days for water absorption, sorptivity, porosity and density tests. Flexural tensile strength and compressive strength of 40 x 40 x 160 mm specimens were measured at the curing age of 7, 28 and 90-day. Mini V-funnel flow time and mini slump flow diameter tests were also conducted to assess rheological properties. The best strength results were obtained from the samples containing between 10% and 25% of GPP as compared to control specimens. GPP15 has the highest pozzolanic activity at the curing age of 28 and 90 days. Replacement of the cement with 10-20% of GPP resulted in mortars which caused a decrease in water absorption, sorptivity and porosity when compared to the control mortar. (c) 2017 Elsevier Ltd. All rights reserved.
Keywords: Self-compacting mortar; Ground pumice powder; Durability properties; Fresh properties; Mechanical properties